EFFECTS OF PRE-COMPETITION ACTIVATION ON OUTCOME PERFORMANCE IN SWIMMING SPRINTERS - Krylov A.I.; Ivchenko E.V.; Ivchenko E.A.; Vinogradov E.O. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify the influence of warm-up intensity and duration predictors on the competitive results of sprint swimmers. Methods and structure of the study. During the work, three warm-up options of similar content were analyzed: long (3000 m), short (1500 m) and high-intensity (1000 m). The swimming time for 100 m and the intermediate swimming time of the first 50 m segment were recorded. The duration and intensity of the warm-up varied. Results and conclusions. It was found that in order to achieve high athletic results in sprint swimming, it is possible to use both long and short (up to 1500 m) warm-up in water – any of the options can be successful. A high-intensity warm-up and a short rest period before the start (10 min) have a decreasing effect on swimming results.